2014
DOI: 10.1111/ffe.12212
|View full text |Cite
|
Sign up to set email alerts
|

Role of constraint on the shift of ductile–brittle transition temperature of subsize Charpy specimens

Abstract: The ductile–brittle transition temperature is not intrinsic to steel but depends on the specimen type and loading mode used for the test. The influence of these parameters is related to the plastic constraint. Here, the constraint is evaluated by the effective T‐stress obtained by the stress difference method on the notch tip stress distribution. From Charpy energy values at different temperatures, it is possible to obtain a material failure master curve where the notch fracture toughness is plotted versus the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…5 for positive or negative values of T. The maximum opening stress is indicated by a black spot only for positive T stress. For negative T stress, this maximum occurs for negative values of opening stress and bifurcation cannot occur because the crack surfaces cannot overlap [11]. The bifurcation angle θ * is given when the first derivative of Equation (9) is equal to zero and the second derivative must be negative.…”
Section: √ଶగ ఙ ഇഇmentioning
confidence: 99%
See 1 more Smart Citation
“…5 for positive or negative values of T. The maximum opening stress is indicated by a black spot only for positive T stress. For negative T stress, this maximum occurs for negative values of opening stress and bifurcation cannot occur because the crack surfaces cannot overlap [11]. The bifurcation angle θ * is given when the first derivative of Equation (9) is equal to zero and the second derivative must be negative.…”
Section: √ଶగ ఙ ഇഇmentioning
confidence: 99%
“…Crack extension is modelled by the finite element method using the CTOA criterion coupled with the node release technique. The node release technique algorithm has been presented in an earlier study [11]. It is based on the assumption that cracks grow step by step, and each step has the length of one mesh element.…”
Section: Node Release Technique For Crack Extensionmentioning
confidence: 99%
“…4 The ductile tearing assessment in a typical engineering critical assessment procedure requires a detailed description of the material fracture resistance, measured by the J-Δa curve. [15][16][17][18] Capelle et al 19 have studied the role of constraint on the shift of the ductile-to-brittle transition temperature. However, previous studies 8- 10 have demonstrated the over-conservatism in J-Δa curves from these standard fracture specimens, including the single-edge-notched bend, SE(B) specimen and the compact tension, C(T) specimen due to the significant crack-front constraint loss in the pipes.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Such constraint difference will impose a marked effect on the measured J-Δa curve. [15][16][17][18] Capelle et al 19 have studied the role of constraint on the shift of the ductile-to-brittle transition temperature. Huang et al 20 have developed constraint-corrected J-Δa curve from standard SE(B) specimens using nine different constraint parameters for pipeline steels based on 3D finite element (FE) analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Evolution of the ratio ffiffiffiffiffi ffi 2πr p :σ θθ K Iwith crack propagation direction in the presence of T stress 54. …”
mentioning
confidence: 99%